Adverse reactions from community directed treatment with ivermectin (CDTI ) for onchocerciasis and loiasis in Ondo State, Nigeria - Otubanjo, O.A. (2008)
Onchocerciasis is an endemic disease in Ondo state, Nigeria. Community directed distribution of ivermectin is currently on-going in some local government areas of the state. Randomly selected persons (2,331 males and 2,469 females) were interviewed using a modified rapid assessment procedure for Loa loa (RAPLOA) to assess community directed treatment with ivermectin. The retrospective study evaluated the coverage, impacts and adverse reactions to the drug treatment. A questionnaire was administered by house-to-house visit in six local government areas, implementing community directed treatment with ivermectin (CDTI) in this bioclimatic zone. A total of 2,398 respondents were reported to have participated in the treatment. The overall ivermectin coverage of 49.96% was recorded (range 0 - 52% in different communities). Adverse reactions from ivermectin administration were experienced in 38% of individuals. Diverse adverse reactions experienced included predominantly itching (18.50%); oedema, especially of the face and the limbs (8.2%); rashes (3.4%) and body weakness (2.4%). Expulsion of intestinal worms occurred in 0.96% of the respondents. The occurrence of adverse reactions in relation to age categories was statistically significant. Neither fatal nor severe adverse reactions were reported by respondents. Significantly, despite experienced adverse reactions, continued participation, acceptability and compliance to ivermectin treatment was expressed by the various communities. This attitude is in consonance with the African Programme for Onchocerciasis Control (APOC) objectives.